Penerapan Metode Penugasan Dalam Meningkatkan Hasil Belajar PAI Siswa Kelas V SDN 03 Sariak Laweh - Muhammad Elri Fahmi; Iswantir Iswantir; Defi Yuslia; Roza Elfira; Desri Wahyuni; Yona Widia Eka Putri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low fine motor skills of V Class Elementary School at UPTD SD N 01 Solok Bio-Bio in Solok Bio-Bio Village. One solution to address this issue is to implement pipette folding activities. This study aims to improve fine reading of Al-Quran at V Class UPTD SD N 01 Solok Bio-Bio in Solok Bio-Bio Village. The research method used in this study is Classroom Action Research (CAR). This classroom action research was conducted in two cycles, with two meetings in each cycle. Data collection techniques used were observation and documentation. The results of this research show animprovement in children's scores from the pre-action phase, Cycle I, to Cycle II, which can be described as follows: In the pre-action phase, 11 children or 55% had low scores (BB), then in Cycle 1, this decreased to 2 children or 10%, and in Cycle II, it became 0 children or 0%. The moderate score (MB) in the pre-action phase was 2 children or 10%, then in Cycle 1, it became 2 children or 10%, and in Cycle II, it became 0 children or 0%. The high score (BSH) in the pre- action phase was 2 child or 10%, then in Cycle 1, it became 2 children or 10%, and at 2 children or 10% in Cycle II. The very high score (BSB) in the pre-action phase was 5 child or 25%, then in Cycle 1, it became 5 children or 25%, and in the end, in Cycle II, it increased to 17 children or 85%. Based on the above research results, the researcher recommends that teachers consider implementing Cart Sort activities as an alternative method to enhance children's fine reading Al-Quran.